Implikasi Penjualan Pakaian Bekas Impor bagi Konsumen di Kota Denpasar - Ni Made Indah Krisna Dewi; Ida Ayu Putu Widiati; I Nyoman Sutama (Jurnal Interpretasi Hukum, 2020)
The sale of imported secondhand clothing is prohibited by the Government because it is in violation and not in accordance with applicable laws and regulations. Regarding import trade, it is regulated in Article 47 paragraph (1) of Law Number 7 of 2014 concerning Trade. The imported secondhand clothing can be categorized as dangerous goods because it circulates freely and without prior checking. Based on the background of the problems that have been described, this research was conducted with the aim of outlining how the arrangements for the implementation of the sale of imported secondhand clothing in the City of Denpasar and how the implications of the sale of imported secondhand clothing for consumers in the City of Denpasar. This study was designed using an empirical research approach, in which this research was conducted according to the real situation in a community or the surrounding environment with the aim of finding facts or legal issues that exist. The results of this study indicated that the regulation of the sale of imported secondhand clothing is regulated in Article 2 of the Regulation of the Minister of Trade of the Republic of Indonesia Number 51/M-DAG/PER/7/2015 concerning Prohibition of Imported Secondhand Clothing, where the secondhand clothing is prohibited from being imported into the territory of the Unitary State Republic of Indonesia because it has an impact on people's health and economy. The implication of the sale of imported secondhand clothing is very detrimental to the community especially in terms of health and economics. The use of imported secondhand clothes can also cause diseases such as itching, tinea versicolor, flu, etc., due to microbial bacteria attached to the secondhand clothes. Therefore, there is a need for socialization regarding these rules to the public and sellers of imported secondhand clothing, as well as enforcement of the rules through Raids against container sheds that distribute imported secondhand clothing to sellers.